2,000 pineapple mushroom blocks distributed for the benefit of the Tuaran community - Mimi Rabita, Abd Wahit (UMPSA, 2024)
TUARAN, 2 March 2024 - A total of 200 residents around Tuaran participated in a workshop producing pineapple mushrooms from the research of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) lecturers led by Associate Professor Dr. Aizi Nor Mazila Ramli by using waste from pineapple plantation as the main substrate for mushroom blocks.